Borderline rejection in ABO‐incompatible kidney transplantation. Issue 8 (28th July 2016) - Sánchez‐Escuredo, Anna; Oppenheimer, Federico; Solé, Manel; Revuelta, Ignacio; Cid, Joan; Lozano, Miguell; Blasco, Miquel; Esforzado, Nuria; Ricart, Maria Jose; Cofán, Federico; Torregrosa, Josep Vicens; Paredes, David; et al.
Abstract: Introduction: The clinical results of ABO‐incompatible (ABOi) and ABO‐compatible (ABOc) kidney transplantation (KT) are similar. Protocol kidney biopsies (PKB) of ABOi transplant recipients show positivity for C4d without evidence of antibody‐mediated rejection (ABMR), but little is known about the histologic progression. Method: We evaluated histologic parameters in PKB at 12 months and also compared clinical outcome at 1 year. This is a prospective observational study conducted between 2009 and 2013. We performed 146/30 ABOc/ABOi consecutive living‐donor KT with PKB as well as additional indication biopsies. In the ABOi group, the desensitization protocol consisted of rituximab, plasma exchange or immunoadsorption, and immunoglobulins. Results: In indication biopsies during the first year, T‐cell‐mediated rejection Banff ≥immunoadsorption was 8.2% vs 6.7% ( P =.561) and ABMR 4.8% vs 13.3% ( P =.095). At 1 year, PKB (ABOc/ABOi) showed differences in borderline rejection lesions (6.8% vs 23.3% [ P =.012]) and in C4d positivity in the ABOi group ( P =.001). Interstitial fibrosis and tubular atrophy (IFTA) lesions (ABOc/ABOi) were 68.4% vs 63.2% ( P =.348). Transplant glomerulopathy was 0.7% vs 3.3% ( P =.373) at 1 year. Conclusions: Our PKB ABOi series shows at 1 year more borderline lesions independent of ABO titers, HLA incompatibility, and the presence of antidonor antibody, but do not show more IFTA nor transplant glomerulopathy. No clinical differences were observed between ABOi and ABO transplants.